External knowledge diversity, competition intensity and innovation performance in logistics: Implications for less versus more innovative industries - Maryam Haji Ali Beigi (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2021)
Purpose: This paper analyzes the association of searching diversely as a strategy to capture external knowledge and that of competition intensity with innovation in logistics. Secondly it studies how these associations interact by examining whether they intensify or mitigate one another when jointly occur. Thirdly, it is explored whether correlations of search diversity, competition intensity and their interaction effect with logistics innovation demonstrate differences in their strength depending on logistics innovativeness of target industries. Design/methodology/approach: By discriminating between diversifying and expanding search scope, a new search mode is identified which is more precise in examining diversity of acquired external knowledge in comparison to search breadth. External search diversity is formulated based on a classification of external sources according to similarities in their knowledge supply. Quantile regression is applied for the purpose of this study due to its ability in estimating different models in different quantiles of the response variable.
Keywords: 330; logistics innovation; search diversity; competition intensity; knowledge management